BUDAYA LUHUR KUPATAN MAKNA DAN NILAI DALAM PEMBELAJARAN PESERTA DIDIK SEKOLAH DASAR - Fatimah, Iis Daniati; Novialita Angga Wiratama; Fera Dwidarti (Jurnal Tunas Pendidikan, 2025)
This article examines the meaning and value of the kupatan tradition for students. The method used is a qualitative method with a descriptive analysis approach that aims to explain how the kupatan tradition has an impact on the value and meaning for students. The results of this study indicate that the kupatan tradition in several regions has its own characteristics. However, these characteristics do not eliminate the meaning of the kupatan tradition itself, which is a form of gratitude to God Almighty. Kupat as a regional specialty food has its own meaning for students. Kupat is closely related in terms of mathematics ketupat has a geometric shape that can be studied by students. Through civic education that reflects the attitude of mutual cooperation, togetherness, harmony and never give up. In the review of kupat language has a variety of meanings seen from the meaning and understanding. The conclusion of the research carried out that through the kupatan tradition can instill good and moral values for students in everyday life.